Dynamic changes of scleral spur length in different accommodation stimuli states - Liugui Chen (Nature Portfolio, 2021)
Abstract This study aimed to evaluate the scleral spur length (SSL) in response to different accommodation stimuli states, as well as the correlation with Schlemm’s canal (SC) and trabecular meshwork (TM). 74 children were recruited for this study. The 0D, − 4D, and − 8.0 D accommodation stimuli state was achieved by looking at a variable distance optotype. The ciliary muscle (CM), scleral spur (SS), SC, and TM were imaged by swept-source optical coherence tomography. The SSL (Method III) increased significantly from 221.56 ± 30.74 μm at base state to 234.99 ± 30.11 μm at − 4D accommodation stimuli state (p = 0.028) and increased to 250.09 ± 29.87 μm at − 8D accommodation stimuli state (p = 0.011). Method III had the largest areas under receiver operating characteristic (ROC) curves (0.798, 95% CI 0.721–0.875). Moreover, CM 1, SC, and trabecular meshwork length (TML) were significantly correlated with SSL (Method III) (p < 0.05). These findings suggest that the contractile ability and compliance of the SS play an important role in maintaining the morphology of the SC. Moreover, the force of accommodation regulates the SC size by increasing the length of SS.